Práticas educativas do acolhimento institucional e o desenvolvimento da autonomia das crianças e adolescentes: “eu acho que ensinei… pra alguém que não sabia” - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This thesis focuses on the study of educational practices in institutional care and the development of autonomy in children and adolescents. The research aims to analyze the relationships between the educational practices occurring within the care institution and the development of autonomy in children and adolescents. Specifically, it seeks to: identify and characterize the educational practices carried out in a children's and adolescents' care institution; analyze the coexistence of educational practices among adults, children, and adolescents in the relationship between care and autonomy; and establish connections between the elements of educational practices in institutional care and the dimensions of the autonomy development process in children and adolescents. The study is characterized as qualitative research, employing content analysis as a tool for organizing and systematizing data, which were obtained through participant observation, interviews, and representational activities. The theoretical and epistemological framework is structured based on the Historical-Cultural Theory. The field study was conducted in a children's and adolescents' care institution in the interior of the State of Pará, involving 4 children, 7 adolescents, and 11 institutional care professionals as participants. The study identified eight educational practices: counseling, play, experience and information sharing, engagement in daily life activities, shared activities, routine establishment, questioning, and guidance, all of which were characterized within the context of the care institution. The analysis of the coexistence of practices and relationships indicated that the actions of care professionals are predominantly instructional, mainly occurring through guidance and counseling, while the actions of children and adolescents are generally related to practical elements, such as daily life activities and play, which are more prevalent in peer relationships. In establishing the relationship between educational practices and autonomy, the study revealed that children's and adolescents' resistance actions and behaviors create tensions that lead to the reconfiguration of the educational practices of care professionals. Furthermore, it was found that the educational practices carried out within the care institution contribute significantly to the development of autonomy in terms of skills and behaviors related to functional activities, such as self-care and self-organization. However, they face challenges in enabling children and adolescents to develop life projects oriented toward emancipation. Thus, this study may contribute to reflections on care practices, particularly educational practices and the pedagogical dimension of institutions, in order to improve care measures. Additionally, it offers valuable contributions to discussions in the field of education.
Keywords: acolhimento institucional; autonomia; práticas educativas; crianças e adolescentes.; institutional care; autonomy; educational practices; children and adolescents; Educação